2011
DOI: 10.1203/pdr.0b013e31823279b1
|View full text |Cite
|
Sign up to set email alerts
|

Functional Impairments at School Age of Children With Necrotizing Enterocolitis or Spontaneous Intestinal Perforation

Abstract: ABSTRACT:We aimed to determine motor, cognitive, and behavioral outcome at school age of children who had either necrotizing enterocolitis (NEC) or spontaneous intestinal perforation (SIP). This case-control study included infants with NEC Bell's stage IIA onward, infants with SIP, and matched controls (1996 -2002). At school age, we assessed motor skills, intelligence, visual perception, visuomotor integration, verbal memory, attention, behavior, and executive functions. Of 93 infants with NEC or SIP, 28 (30%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 24 publications
1
38
0
Order By: Relevance
“…b). Similar findings were reported by Roze et al . in a case–control study of preterm children with necrotizing enterocolitis or intestinal perforation.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…b). Similar findings were reported by Roze et al . in a case–control study of preterm children with necrotizing enterocolitis or intestinal perforation.…”
Section: Resultssupporting
confidence: 91%
“…c). These inflammatory conditions thus lead to a considerable increased risk of impairment of fine motor skills, with ORs between 3 and more than 5 . These studies suggest a relation between abnormal outcomes and white matter injury due to an inflammatory response …”
Section: Resultsmentioning
confidence: 88%
“…So far, most studies on the neurodevelopment of VLBWI reported outcome at the age of 18-36 months 17 or used data of cohorts from the 1990s 18 which are not necessarily comparable with recent cohorts who have a decreased short-term morbidity including NEC [19][20][21][22] . In one study, the authors found a reduced IQ score in children with a history of gastrointestinal disease (NEC or SIP) 11 . In our study, we made a clear distinction between surgical NEC and surgical SIP based on pathophysiological and macroscopical (as defined by attending surgeon) criteria.…”
Section: Discussionmentioning
confidence: 99%
“…In our matched cohort, we found decreased head circumferences in the NEC and SIP group. Some studies report substantial growth failure (<10 th percentile) for weight, length, and head circumference in infants with NEC 26 , but results were conflicting 11 . One study examining head biometrics in magnet resonance imaging (MRI) Figure 1.…”
Section: Discussionmentioning
confidence: 99%
“…1, 2, 3 Survivors of NEC have longer hospital stay and are at risk for long-term nutritional and neurologic problems. 4, 5, 6 A major challenge toward improving outcomes is identifying and treating infants in the early stages of NEC, when clinical signs may be subtle and nonspecific. Once more definitive signs appear, adverse outcomes such as extensive bowel necrosis leading to death or short bowel syndrome are more likely.…”
Section: Introductionmentioning
confidence: 99%